2018
DOI: 10.1016/j.buildenv.2017.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Performance analysis of pulsed flow control method for radiant slab system

Abstract: We present a novel pulsed flow control method (PFM) using a two-position valve to regulate the capacity of radiant slab systems. Under PFM, the on-time duration of the valve is short (compared to all prior work, e.g. 4-minute), and fixed, while the off-time varies. We present a novel, open-source, finite difference model that assesses three-dimensional transient slab heat transfer, accounting for the transient heat storage of the pipe fluid. Sensitivity analysis results indicate the dominant factors influencin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…SkyLab was developed in collaboration with Lawrence Berkeley National Laboratory (LBNL) drawing reference to the concepts of FLEXLAB® [25] in LBNL. SkyLab enables controlled laboratory studies of building systems and occupant comfort, similar to those reported in [25] - [29]. SkyLab has 0.257-m-thick exterior walls, which are built up of gypsum firestop plasterboards, rock wool insulations and aluminium composite panel in powder coated finish (external cladding).…”
Section: Bca Skylab Test Bed Facilitymentioning
confidence: 99%
“…SkyLab was developed in collaboration with Lawrence Berkeley National Laboratory (LBNL) drawing reference to the concepts of FLEXLAB® [25] in LBNL. SkyLab enables controlled laboratory studies of building systems and occupant comfort, similar to those reported in [25] - [29]. SkyLab has 0.257-m-thick exterior walls, which are built up of gypsum firestop plasterboards, rock wool insulations and aluminium composite panel in powder coated finish (external cladding).…”
Section: Bca Skylab Test Bed Facilitymentioning
confidence: 99%
“…Sui et al [13] observed that increasing the start and stop frequency of the pump during a given cooling period increased the cooling capacity of a tubes-embedded envelope cooling system. Liu et al [14] proposed intermittent controls based on the minimum outdoor air temperature and the average water supply and return temperature via CFD simulation Tang et al [15] proposed a novel pulse flow control method that allowed for a 27% reduction of the supply water flow at 50% load operation, and it made the radiant surface temperature distribution more uniform with more accurate control.…”
Section: Introductionmentioning
confidence: 99%
“…[26]. FLEXLAB provides a controlled, highly instrumented building technology testbed that enables assessing the indoor environment and energy savings potential under a range of conditions expected to occur in the real world [27][28][29][30][31]. FLEXLAB is used to support the ASHRAE 140 framework to improve characterization of building energy modeling engine accuracy and to provide a consistent validation framework that provides confidence in energy simulations [32].…”
Section: Introductionmentioning
confidence: 99%